Synergistic ideas in oncology: prospects for practical implementation - E. S. Evstratova; V. G. Petin (Исследования и практика в медицине, 2020)
The review is devoted to the analysis of the problem of synergistic ideas application in oncology after simultaneous combined application of agents. An example of the determination and quantification of the synergistic enhancement ratio is presented. It is emphasized that independent addition is determined by product of probabilities of the effects induced by each agent applied separately. Elevated temperatures synergistically enhance the lethal effect of ionizing radiation and chemical compounds used in the treatment of cancer. Analyzing the dependence of the synergistic effect on the acting temperature after its simultaneous application with ionizing radiation or cisplatin, the existence of an optimal temperature ensuring the greatest synergistic interaction was shown for cultured mammalian and yeast cells. The universal regularities of the manifestation of synergism, independent on the agents, biological objects and tests used, are noted. The greatest synergy is observed with the simultaneous application of agents. The synergism recorded as a result of the combined effects of two factors is observed only with a certain ratio of the effects induced by each agent. Synergism depends on the intensity of the factors used — the current temperature, the dose rate of ionizing radiation or the concentration of chemical agents. These universal patterns have been demonstrated for proand eukaryotic cells, including oncological origin. The existence of universal patterns of synergism indicates the need to develop a new paradigm and theoretical model of synergism, which should take into account the identified patterns. An original biophysical concept of synergistic interaction is proposed. Concrete results are presented that demonstrate the possible ways of using the ideas of synergism in oncology by achieving the greatest synergistic enhancement ratio for the combined effects of various physical and chemical agents. It is concluded that the knowledge and the application of the ideas and general patterns of synergy described in this paper can be useful for specialists using the simultaneous action of various agents to optimize combined treatment methods in modern oncology.